Reading « Hairstories » and « Hairitages » in Léonora Miano’s and Rokhaya Diallo’s Works - Montlouis-Gabriel, Johanna (Études littéraires africaines, 2019)
This article aims at analyzing a distinctive symbol of black women : their hair. In the last decade, many Afro-feminists (in America, France, the Caribbean and many other countries) have been reclaiming hair as part of their heritage and embracing its natural « nappy » state (for « natural » and « happy »). In my analysis of hair, I will compare and contrast how Léonora Miano in her novel Blues pour Élise and her short story « Corpus Christi » and Rokhaya Diallo, in her graphic novel Pari(s) d’amies !, seek to replace the self-loathing and deprecating narratives that women of color are commonly told about their hair and their physique. Instead, they reclaim these negative images of hair as well as of other bodily features by self-love and self-fulfillment. While some characters may still be struggling with this idea, I argue that the repossessing of one’s own hair constitutes a performative act.